Pengetahuan dan Sikap Ibu Rumah Tangga dalam Pencegahan Kanker Servik - Putri Andanawarih; Ni’matul Ulya; Swasti Artanti (Prodi D III Kebidanan Fakultas Ilmu Kesehatan Universitas Ibrahimy, 2024)
Cervical cancer caused by HPV (human papillomavirus) usually attacks women aged between 35 and 55 years and ranks second as the type of cancer most commonly experienced by Indonesian women. Early detection of cervical cancer is done with the visual acetic acid test (IVA). The aim of this research was to determine the knowledge and attitudes of housewives in preventing cervical cancer in the Pringrejo Village area. This research used a cross-sectional method with the Kolmogorov Smirnov reliability test with a sample size of 100 respondents. Both tests were calculated using SPSS version 17 for Windows. The results of the research show that age, education, economic status and knowledge influence the attitudes and behavior of housewives regarding cervical cancer with a p value for each characteristic <0.10. In the results, job characteristics have no relationship with the attitude of housewives in preventing cervical cancer because the p value is > 0.10. With this research, it is hoped that health workers can provide clear information about cervical cancer to the wider community, especially housewives.